Evaluation of a new tuberculosis-related interferon gamma release assay for tuberculosis infection diagnosis in Huzhou, eastern China - Fuchu Qian; Weihong Wang; Zhihong Qiu; Yiqun Shen; Jiangfang He; Dongli Li; Jing Zhong; Licheng Dai (Wolters Kluwer Medknow Publications, 2013)
Objective: To compare the performance of a new tuberculosis-related interferon gamma release assay (TB-IGRA) with that of QuantiFERON-TB Gold In-Tube (QFT-GIT) for TB infection diagnosis in China. Materials and Methods: A total of 458 active TB patients and 378 healthy individuals were enrolled. Among the 458 active TB patients, 395 had pulmonary TB and 63 had extra-pulmonary TB. The blood samples were collected from the active TB patients and health controls; then TB-IGRA and QFT-GIT were used to detect interferon gamma (IFN-γ) levels. Results: The sensitivity, specificity, positive predictive value, and negative predictive value in TB infection diagnosis for active TB by the TB-IGRA were 83.4%, 94.2%, 94.5%, and 82.4%, respectively. For QFT-GIT, the sensitivity, specificity, positive predictive value, and negative predictive value in TB infection diagnosis for active TB were 81.4%, 97.1%, 97.1%, and 81.2%, respectively. Conclusions: TB-IGRA had a high sensitivity and specificity for TB infection; it could be comparable with the QFT-GIT assay. It might be a powerful assisting tool for TB infection diagnosis in the Chinese clinical setting.